Pelatihan Pembuatan Minuman Berbahan Dasar Kopi dan Komoditi Lokal Bagi Pengelola Badan Usaha Milik Desa (Bumdes) dan Kelompok Sadar Wisata (Pokdarwis) Barista: Desa Wisata Ngargoretno, Kecamatan Salaman, Kabupaten Magelang, Jawa Tengah - Budi Wibowo; Nurdin Hidayah; Mochammad Nurrochman; Herlan Suherlan (Sekolah Tinggi Pariwisata AMPTA Yogyakarta, 2022)
Training on Making Coffee-Based Drinks and Local Commodities for Village Owned Enterprises (Bumdes) and Barista Tourism Awareness Groups (Pokdarwis) in the Tourism Village of Ngargoretno, Salaman District, Magelang Regency, Central Java. This community service activity aims to increase basic knowledge about making coffee drinks, as well as increase the entrepreneurial spirit of managers of Badan Usaha Milik Desa (BUMDES) and Kelompok Sadar Wisata (Pokdarwis) Barista in the Tourism Village of Ngargoretno, Salaman District, Magelang Regency, Central Java. The activity was held at Kang Im Kandang (Menoreh Ngargoretno Tourist Information Center) which was attended by 35 participants. The delivery method is carried out with interactive and demonstrative counselling techniques, with the aim of transforming knowledge, attitudes and skills as well as achieving prosperous rural communities. The results of the activity showed an increase in the skills and understanding of the participants about the use and knowledge of the coffee plant, starting from the benefits, uses, processing and elements contained therein, as well as in terms of processing plantation products (coffee) from the garden to being served in a cup, as well as motivation. and the follow-up of participants in making, producing and even consuming their own beverage products along with the use of other commodities was successfully increased through this activity